Hybrid Point-Group Target Tracking Using Angle-Only Measurements with Decoy Flares - Guo, Xiaoxiao; Lan, Jian; Xi, Ruiqing (IEEE transactions on aerospace and electronic systems, 2025)
In aerial combat, an infrared-guided missile is often misled by aircraft-launched decoy flares and then loses the aircraft which is the true target of interest. Target tracking with decoy flares is challenging, as trajectories formed by the target and decoy flares are too similar to distinguish. This becomes more serious when tracking with angle-only measurements provided by the infrared-guided missile, because the target trajectory is hard to estimate accurately. In practice, the motion of a decoy flare is only affected by gravity and atmospheric drag. Decoy flares thus have special dynamics which differ from that of the target. Utilizing this particularity, this paper proposes a framework named multiple hypothesis tracking of hybrid point-group targets (MHT-HPGT) to distinguish the target from decoy flares. First, all decoy flares are treated as a target group referred to as a decoy flare group, because they have similar initial states and dynamics. The target is still treated as a point target. Secondly, the MHT recursion is extended to allow for at most one measurement per point target and multiple measurements per target group at one moment. Two simplifications of the framework are proposed. Then, to track the decoy flare group using angle-only measurements, a random-matrix-based model for kinematic state evolution, extension evolution, and measurements of the group is derived. Finally, the implementation of the MHT-HPGT is presented. Simulation results demonstrate the effectiveness of the proposed approach compared with existing tracking methods.